Methodology of the investigation of murders committed with particular cruelty - Ісагова Наталія Магомед кизи (My University, 2025)
The dissertation formulates scientific conclusions, recommendations, proposals that may have an important theoretical significance for forensic science in the course of further scientific development and improvement of the methodology of investigation of murders committed with particular cruelty, and be practically applied in the practice of pre-trial investigation bodies. The state of scientific development of the methodology of the investigation of murders committed with particular cruelty, the forensic classification of crimes of this type, as well as the content of the elements of their forensic characteristics: the method of committing crimes of this type, the identity of the criminal and the victim, and a typical trace picture have been studied. It has been established that a number of domestic experts in the field of criminology devoted scientific works to the problem of the formation of the methodology of investigation of criminal offenses, including at the monographic level. However, the most numerous are scientific searches in the field of development and improvement of methods of investigation of intentional murders based on a certain defining feature (the identity of the criminal, the method and conditions of the commission, the method of concealing the murder or a combination of several features). Attention is focused on the fact that the forensic classification of crimes should include forensic features that would indicate the peculiarities of the way the crime was committed, its situation, the trail picture, etc., that would determine the direction of the investigation, determine the ways of finding the guilty person. On the basis of a systematic analysis of scientific literature and empirical sources, namely the materials of judicial practice regarding the investigation and trial of murders committed with particular cruelty, the grounds for the classification of crimes of this type have been identified. An attempt was made to provide a forensic characterization of murders with particular brutality by revealing its elements: the method of committing the crime (consisting of preparation, direct commission and concealment of traces of the crime), the setting, a typical trace pattern, the identity of the criminal, the identity of the victim. On the basis of a systematic analysis of the materials of investigative and judicial practice, it was established that murders with particular brutality are almost never committed with preliminary preparation for the commission of the crime. The only preparatory action carried out by a criminal that can be considered preparation for committing a particularly brutal murder is the selection and bringing to the scene of the crime of the instrument of its commission. The most common methods of committing murders with particular cruelty, as well as the means used in this case, were also revealed. We found no signs of concealment of the committed crime, a significant proportion of crimes of the investigated type (about 20% of investigated criminal proceedings) were committed in the presence of witnesses, i.e. under conditions of obviousness. A number of factors influencing the choice of a tool for committing a particularly brutal murder, as well as correlations between the method of execution and the identity of the criminal and the identity of the victim, have been established. The situation of committing murders with particular brutality was studied as an element of the forensic characteristics of crimes of this type, namely the place and time of commission. A typical "trace picture" of murders committed with particular brutality is: the corpse of the victim; injuries on it; the state of clothing of the corpse; tools and means of crime (parts thereof); traces of blood, hands, feet, teeth of the criminal and the victim; traces of struggle found at the scene and on the victim's body and clothes; traces of vehicles, tools of crime; parts of clothing; micro objects, etc. We believe that the most important traces of a particularly brutal murder are the traces left on the victim's body, that is, on the corpse, the visual inspection of which at the scene allows us to put forward primary versions about the way the crime was committed, the sequence of criminal actions, the tools and means used by the criminal, as well as the probable number of criminals, their physical strength, skills, etc. Based on the results of a systematic analysis of statistical data for 2016-2023. regarding persons who have committed murders with particular cruelty, i.e. a criminal offense provided for in clause 4, part 2 of Article 115 of the Criminal Code of Ukraine, provided a criminalistic description of the person of the criminal (gender, age, education, the proportion of persons who had previously committed criminal offenses, who at the time of the announcement of the suspicion had not had their criminal record cleared or exonerated, committed the investigated type of crime by a group, propensity for manifestations of aggression, violence and cruelty, tendency to use alcohol and drugs) and the victim. It was found that the majority of victims (victims of crime) are female (67%) and male (33%), the share of minors is (12%). At the same time, minors become victims of murder with particular cruelty together with an adult, usually one of the parents (in 100% of established cases). It was established that in the vast majority of cases the criminal and the victim knew each other. In the majority of established cases of murder committed with particular brutality (more than 70%), there was an existing conflict between the victim and the perpetrator, which arose suddenly, or a long-term conflict or hostile relationship. Circumstances to be established during the pretrial investigation are factual data systematized on the basis of the norms of criminal and criminal procedural law, the establishment of which ensures a complete and comprehensive study of the subject of evidence, which is necessary for the implementation of the tasks of criminal proceedings, during its pretrial investigation and trial. They are the circumstances regarding the time, place, and manner of committing the murder with particular cruelty; information about the identity of the criminal, the victim, the "victim-criminal" relationship and other circumstances. The content of each group of circumstances is revealed, procedural and forensic means of establishing them are outlined. The organizational and tactical aspects of the inspection of the scene, which is carried out at the place of the murder with particular cruelty, as well as the specifics of the appointment and conducting of the forensic medical examination of the corpse, are considered. In our opinion, the results of these procedural actions affect the formation of the investigative situation and the criminalistic versioning at the initial stage of the pre-trial investigation of a murder committed with particular cruelty, and therefore the conditional algorithm of the investigation. There is a defined circle of circumstances that immediately during the examination or following its results may have the character of knowledge of a high degree of probability, as well as those regarding which, on the basis of the examination results, only separate forensic versions, i.e., reasonable assumptions, can be put forward. In order to comply with the principle of completeness of the inspection of the scene of the incident, the powers and directions of activity of the specialists involved in conducting the inspection of the scene of the incident have been established. The tasks of the forensic medical expert on the examination of the corpse at the scene are considered separately. The examination of biological traces (blood, hair, particles of the epithelium, brain matter, etc.) is of great importance during the examination of the place where the murder was committed with particular cruelty. An extremely important feature of recording the course of the inspection of the scene of the incident is the use of modern technical means of recording, the possibilities of which are currently very diverse (3D scanners, etc.), and their advantages and disadvantages are considered. The specifics of conducting a forensic medical examination of a corpse in criminal proceedings about murders committed with particular cruelty are established, as well as the directions of using factual data contained in the conclusion of a forensic medical expert based on the results of its conduct are determined. The scientific definitions of the investigative situation proposed in the forensic literature were analyzed, and it was determined that it is both an imaginary, abstract, artificial information model that is the result of the generalization of the practice of investigating criminal offenses of a particular type, and a real set of conditions, given factors that exist at a certain stage of the investigation . On the basis of a systematic analysis of scientific forensic sources devoted to the theory of the investigative situation and the materials of judicial and investigative practice we have studied regarding the investigation of murders committed with particular cruelty, a system of typical investigative situations of the initial and subsequent stages of the investigation of murders committed with particular cruelty is proposed. It was concluded that since the investigation of murders with particular brutality begins with an urgent investigative (search) action, which can be carried out before the relevant information is entered into the EDPR, namely, an inspection of the scene of the incident, and the investigative situation as a real set of conditions, data factors that exist at the initial stage stage of the investigation, is determined taking into account its results, intermediate and final, as well as taking into account that the appointment of a forensic medical examination of a corpse in order to establish the cause of death is the duty of the investigator, the prosecutor, provided for in clause 1, part 2 of Article 242 of the Criminal Code of Ukraine, therefore it is not appropriate to include these procedural actions in the investigator's algorithm of actions in every investigative situation. A number of tactical techniques and recommendations are proposed that can be used to increase the effectiveness of the interrogation of a suspect in a particularly brutal murder. The conditions affecting the formation of psychological contact between the investigator and the interrogated suspect have been determined. The factors that contribute to the creation of a conflict-free interrogation situation, in which the suspect gives mostly truthful testimony, and the interrogation itself does not pose significant difficulties for the investigator, have been established. Definite tactical techniques and recommendations for conducting interrogations carried out in conflict investigative situations (giving false testimony, declaring a false alibi, slandering another person) or the suspect generally chooses the tactic of refusing to testify in order not to harm himself. The expediency of appointment and possibilities of a number of forensic examinations (forensic-genomic, fire-technical, computer-technical, forensicpsychiatric examination) were considered. A list of covert investigative (detective) actions, the implementation of which can be effective in the course of the investigation of murders with particular cruelty, is proposed, and the tasks that can be solved by their implementation are defined.

У дисертації сформульовано наукові висновки, рекомендації, пропозиції, що можуть мати важливе теоретичне значення для криміналістичної науки в ході подальшої наукової розробки та удосконалення методики розслідування вбивств, вчинених з особливою жорстокістю, та бути практично застосованими в практиці органів досудового розслідування. Досліджено стан наукової розробленості формування методики розслідування вбивств, вчинених з особливою жорстокістю, криміналістична класифікація злочинів цього виду, а також зміст елементів їх криміналістичної характеристики: способу вчинення злочинів цього виду, особи злочинця та потерпілого, типової слідової картини. Встановлено, що проблематиці формування методики розслідування кримінальних правопорушень присвячували наукові праці низка вітчизняних фахівців у сфері криміналістики, у тому числі й на монографічному рівні. Проте найчисельнішими є наукові пошуки у сфері розробки й удосконалення методик розслідування умисних вбивств за певною визначальною ознакою (особа злочинця, спосіб та умови вчинення, спосіб приховання вбивства або поєднання декількох ознак). Акцентовано увагу на тому, що криміналістична класифікація злочинів має включати криміналістичні ознаки, які б вказували на особливості способу вчинення злочину, його обстановки, слідової картини тощо, які б обумовлювали напрямок розслідування, визначали шляхи пошуку винуватої особи. На підставі системного аналізу наукової літератури та емпіричних джерел, а саме матеріалів судової практики щодо розслідування та судового розгляду вбивств, вчинених з особливою жорстокістю, виокремлені підстави для класифікації злочинів цього виду. Зроблено спробу надати криміналістичну характеристику вбивствам з особливою жорстокістю через розкриття її елементів: спосіб вчинення злочину (складається з підготовки, безпосереднього вчинення та приховання слідів злочину), обстановка, типова слідова картина, особа злочинця, особа потерпілого. На підставі системного аналізу матеріалів слідчо-судової практики, встановлено, що вбивства з особливою жорстокістю майже не вчиняються з попередньою підготовкою до вчинення злочину. Єдиною підготовчою дією, яка реалізується злочинцем та може вважатися підготовкою до вчинення вбивства з особливою жорстокістю, є обрання та принесення на місце вчинення злочину знаряддя його вчинення. Також виявлені найбільш поширені способи вчинення вбивств з особливою жорстокістю, а також засоби, що при цьому застосовуються. Ознак приховання вчиненого злочину нами встановлено не було, значна частка злочинів досліджуваного виду (близько 20% досліджених кримінальних проваджень) вчинялася в присутності свідків, тобто за умов очевидності. Встановлені низка факторів, що впливають на вибір знаряддя вчинення вбивства з особливою жорстокістю, а також кореляційні зв’язки між способом вчинення та особою злочинця, особою потерпілого. Досліджено обстановку вчинення вбивств з особливою жорстокістю як елемент криміналістичної характеристики злочинів цього виду, а саме місце та час вчинення. Типову «слідову картину» вбивств, вчинених з особливою жорстокістю становлять: труп потерпілого; тілесні ушкодження на ньому; стан одягу трупа; знаряддя та засоби злочину (їх частини); сліди крові, рук, ніг, зубів злочинця і потерпілого; сліди боротьби, що виявлені на місці події та на тілі, одязі потерпілого; сліди транспортних засобів, знарядь учинення злочину; частини одягу; мікрооб’єкти тощо. Вважаємо, що найбільш важливими слідами вчинення вбивства з особливою жорстокістю є сліди, залишені на тілі потерпілого, тобто на трупі, візуальний огляд яких на місці події дозволяє висувати первинні версії про спосіб вчинення злочину, послідовність злочинний дій, застосовані злочинцем знаряддя та засоби, а також ймовірну кількість злочинців, їх фізичну силу, навички тощо. На підставі результатів системного аналізу статистичних даних за 2016 – 2023 р.р. щодо осіб, які вчинили вбивство з особливою жорстокістю, тобто кримінальне правопорушення, передбачене п. 4 ч. 2 ст. 115 КК України, надано криміналістичну характеристику особі злочинця (стать, вік, освіта, частка осіб, які раніше вчиняли кримінальні правопорушення, у кого на момент оголошення про підозру судимість не знята і не погашена, вчинення досліджуваного виду злочину групою, схильність до проявів агресії, насильства та жорстокості, схильність до вживання алкоголю та наркотиків) та потерпілого. З’ясовано, що здебільшого потерпілими (жертвами злочину) є особи жіночої (67%) та чоловічої (33%) статі, частка неповнолітніх становить (12%). При цьому неповнолітні стають жертвами вбивства з особливою жорстокістю разом з дорослим, як правило одним із батьків (у 100% встановлених випадків). Встановлено, що в переважній більшості випадків злочинець та жертва знали один одного. У більшості встановлених випадків вчиненого вбивства з особливою жорстокістю (понад 70%) був наявний конфлікт між жертвою та злочинцем, який виник раптово, або довготривалий конфлікт чи неприязні стосунки. Обставинами, що підлягають встановленню в ході досудового розслідування є обставини щодо часу, місця, способу вчинення вбивства з особливою жорстокістю; відомості про особу злочинця, потерпілу особу, зв’язок «потерпілий-злочинець» та інші обставини. Розкрито зміст кожної групи обставин, окреслені процесуальні й криміналістичні засоби їх встановлення. Розглянуті організаційно-тактичні аспекти огляду місця події, що проводиться на місці вчинення вбивства з особливою жорстокістю, а також особливості призначення та проведення судово-медичної експертизи трупа. На наш погляд, результати саме цих процесуальних дій впливають на формування слідчої ситуації та на криміналістичне версіювання на початковому етапі досудового розслідування вбивства, вчиненого з особливою жорстокістю, а отже на умовний алгоритм розслідування. Визначене коло обставин, що одразу в ході огляду або за його результатами можуть мати характер знання високого ступеня ймовірності, а також ті, з приводу яких на підставі результатів огляду можуть лише висуватися окремі криміналістичні версії, тобто обґрунтовані припущення. З метою дотримання принципу повноти огляду місця події встановлені повноваження та напрями діяльності залучених спеціалістів в проведенні огляду місця події. Окремо розглянуті завдання судово-медичного експерта з огляду трупа на місці події. Важливе значення в ході огляду місця вчинення вбивства з особливою жорстокістю має огляд біологічних слідів (крові, волосся, часток епітелію, мозкової речовини тощо). Надзвичайно важливою особливістю фіксування ходу огляду місця події є застосування сучасних технічних засобів фіксації, можливості яких наразі дуже різноманітні (3D сканерів тощо), розглянуто їх переваги й недоліки. Встановлені особливості проведення судово-медичної експертизи трупа у кримінальних провадженнях про вбивства, вчинені з особливою жорстокістю, а також визначені напрями використання фактичних даних, що містяться у висновку судово-медичного експерта за результатами її проведення. Проаналізовані запропоновані в криміналістичній літературі наукові визначення слідчої ситуації, визначено, що нею є як уявна, абстрактна, штучна інформаційна модель, яка є результатом узагальнення практики розслідування кримінальних правопорушень окремого виду, так і реальна сукупність умов, даних факторів, що існують на певному етапі розслідування. На підставі системного аналізу наукових криміналістичних джерел, присвячених теорії слідчої ситуації та вивчених нами матеріалів судово-слідчої практики щодо розслідування вбивств, вчинених з особливою жорстокістю, запропонована система типових слідчих ситуацій початкового та подальшого етапів розслідування вбивств, вчинених з особливою жорстокістю. Зроблено висновок, що оскільки розслідування вбивств з особливою жорстокістю розпочинаються проведенням невідкладної слідчої (розшукової) дії, що може проводитися до внесення відповідних відомостей до ЄРДР, а саме оглядом місця події, а слідча ситуація як реальна сукупність умов, даних факторів, що існують на початковому етапі розслідування, визначається враховуючи його результати, проміжні та кінцеві, а також враховуючи, що призначення судово-медичної експертизи трупа з метою встановлення причин смерті є обов’язком слідчого, прокурора, передбаченим п. 1 ч. 2 ст. 242 КПК України, тому не доцільно включати ці процесуальні дії до алгоритму дій слідчого в кожній слідчій ситуації. Запропонована низка тактичних прийомів та рекомендацій, що можуть бути використані для підвищення ефективності проведення допиту підозрюваного у вбивстві з особливою жорстокістю. Визначено умови, що впливають на формування психологічного контакту слідчого і допитуваного підозрюваного. Встановлено фактори, які сприяють створенню безконфліктної ситуації допиту, в якій підозрюваний дає переважно правдиві показання, а сам допит не становить значних труднощів для слідчого. Визначені тактичні прийоми та рекомендації для проведення допитів, що здійснюються у конфліктних слідчих ситуаціях (давання неправдивих показань, заявлення хибного алібі, обмова іншої особи) або підозрюваний взагалі обирає тактику відмовлятися від давання показань з метою не зашкодити собі. Розглянуто доцільність призначення і можливості низки судових експертиз (судово-геномної, пожежно-технічної, коп'ютерно-технічної, судово-психіатричної експертизи). Запропоновано перелік негласних слідчих (розшукових) дій, проведення яких може бути ефективним в ході розслідування вбивств з особливою жорстокістю, визначено завдання, що можуть бути вирішені шляхом їх проведення.
Методика розслідування вбивств, вчинених з особливою жорстокістю
Methodology of the investigation of murders committed with particular cruelty
Keywords: криміналістична методика; досудове розслідування; вбивство з особливою жорстокістю; криміналістична характеристика; спосіб вчинення злочину; особа злочинця; потерпілий; початковий етап розслідування; обставини; що підлягають встановленню; типові слідчі ситуації; організація і тактика слідчих (розшукових) дій; допит підозрюваного; використання спеціальних знань; судова експертиза; негласні слідчі (розшукові) дії; forensic technique; pre-trial investigation; murder with particular cruelty; forensic characteristics; method of committing the crime; identity of the criminal; victim; initial stage of the investigation; circumstances to be established; typical investigative situations; organization and tactics of investigative (search) actions; interrogation of the suspect; use special knowledge; forensic examination; covert investigative (search) actions